Schizophrenia between evidence, human rights and practice: The S3 guideline 2025 as a legal and psychiatric challenge - Pfeifer, Anja; Mrázová, Mariana (Jurnal Cita Hukum, 2026)
The paper examines the S3 Guideline Schizophrenia 2025 of the German Society for Psychiatry, Psychotherapy, Psychosomatics, and Neurology (DGPPN) as a turning point in modern psychiatry. The paper aims to explore how this living guideline integrates evidence-based medicine, legal regulations, and human rights standards into a unified framework of psychiatric care. Using a qualitative analysis of the guideline's structure, legal references, and participatory development process, the study identifies its methodological innovations and practical challenges. The results highlight that the guideline promotes shared and supported decision-making, empowerment, and recovery-oriented care while defining coercion as a measure of last resort. It establishes psychiatry as a legally constituted field where autonomy, protection, and professional responsibility must be continuously balanced. However, discrepancies persist between the normative standards of the guideline and institutional practice, mainly due to structural and resource limitations. The paper concludes that the S3 Guideline Schizophrenia 2025 represents both a medical and legal policy instrument, setting the foundation for human rights–based psychiatry in Germany and beyond.